PENGEMBANGAN PERMAINAN MAHKOTA BERTEMAN UNTUK PEMBELAJARAN MENGENALKAN KONSEP DAN LAMBANG BILANGAN PADA ANAK USIA DINI - Ayu - Asmah; Tri Candra Wulandari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2018)
Games for growing and developing early childhood provides opportunity to be able to explore and interact with the surrounding environment. A good game form for early childhood is an educative game, a game that stimulates the child's thinking power and helps to optimize aspects of his development. The phenomenon of learning in early childhood at this time is more directed to the academic, so the principle of learning while playing is replaced with worksheets. The purpose of this study is to produce a suitable game of mahkota berteman to be used for learning to introduce concepts and symbols of numbers in early childhood, and improve the ability of early childhood in recognizing the concept and symbol of numbers. The study was conducted in ten stages according to Dick and Carey's Development Research theory (2011), (1) Identity Instructional Goal, (2) Conduct Instructional Analysis, (3) Analyze Learners and Contexts, (4) Write Performance Objectives, (5) Develop Assessment Instrumens, (6) Develop Instructional Strategy, (7) Develop and Select Instructional Materials, (8) Design and Conduct Formative Evaluation of Instruction, (9) Revise Instruction, (10) Design And Conduct Summative Evaluation. The results showed that mahkota berteman gamers were eligible for learning to introduce the concept and symbol of numbers in early childhood. Based on the data analysis of field test results using T test shows that the significance obtained by 0.000 is smaller on the significance used in this research that is 0,05 (sig = 0,000 <0,05), thus H0 is rejected and H1 accepted. So the result this development research can be concluded that after using the mahkota berteman game befriending the ability of children in knowing the concept and the symbol of numbers to be better.